(untitled) (Research, Society and Development, 2022)
Do more democratic countries have higher literacy rates? In this work, we seek to answer this question and, for that, we selected a sample of 54 developing countries distributed among Africa, America and the Caribbean. For this endeavor, we used the indicators per capita income, democracy index, Human Development Index and literacy rate for the year 2015. After analyzing the data, we found a strong correlation between Literacy and HDI (r = 0.847; p = 6.564E-016), moderate correlation between literacy rate and democracy (r = 0.502; p = 0.000108) and correlation between GDP per capita and Literacy was not significant (r = 0.337; p = 0.005).